Cover Image. Issue 2 (9th February 2018) - Standen, Vivien G.; Santoro, Calogero M.; Arriaza, Bernardo; Coleman, Drew
Abstract : The cover image shows an artificial mummy, adult male, modeled with clay (5000 BP), of the Chinchorro Culture, from the Museo Arqueológico San Miguel de Azapa, Universidad de Tarapacá, Arica, Chile. The image is based on the Research Article Hunting, Gathering, and Fishing on the Coast of the Atacama Desert: Chinchorro Population Mobility Patterns Inferred from Strontium Isotopes by Vivien G. Standen, DOI10.1002/gea.21594 . Photo Credit: Vivien G. Standen.